Automated Scalable Spray Coating of SnO2 for the Fabrication of Low‐Temperature Perovskite Solar Cells and Modules. Issue 5 (6th February 2020) - Taheri, Babak; Calabrò, Emanuele; Matteocci, Fabio; Di Girolamo, Diego; Cardone, Giorgio; Liscio, Andrea; Di Carlo, Aldo; Brunetti, Francesca
Abstract : In the renewable energy field, the use of hybrid perovskite materials has opened up new directions to fabricate cost‐effective and highly efficient photovoltaic devices. Despite impressive power conversion efficiency (PCE), exceeding 25.2%, demonstrated on lab‐scale devices, scalability and stability of device are still topical issues. In this context, large‐area deposition procedures and automated fabrication protocols are required to achieve high throughput serial production of modules and panels. In this work, a spray‐coated tin oxide (SnO2 ) layer processed at low temperature for the realization of planar perovskite solar cells (PSCs) and modules is demonstrated. Using sprayed Np‐SnO2 as the electron transport layer (ETL), a CH3 NH3 PbI3 ‐based solar device shows a maximum PCE of 16.77% (avg. 15.01%) comparable to 17% (avg. 15.5%) with respect to spin‐coated Np‐SnO2 . Unencapsulated spray‐ and spin‐coated PSCs stored in 25 °C and 50% relative humidity show shelf life stability by retaining 85% of the initial PCE value after more than 1000 h. Moreover, the feasibility of fabrication of the modules with 15 cm 2 active area is demonstrated, which reaches 9.37% of PCE from uniform spray‐deposited SnO2 film on a large area (20 × 20 cm 2 ). Abstract : Research in the direction of perovskite solar cells (PSCs) industrialization requires the development of automated, reliable, large‐area deposition procedures. In this article, a spray‐coated tin oxide (SnO2 ) layer processed at low temperature for the realization of planar direct PSCs and modules (20 × 20 cm 2 ) is shown, which achieve an efficiency of 16.77% and 9.37%, respectively.